1998
DOI: 10.1159/000017344
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde 3-Phosphate Dehydrogenase Abnormality in Metabolically Stressed Huntington Disease Fibroblasts

Abstract: Huntington disease (HD) fibroblasts subjected to stress exhibit an enzyme profile that is different from that exhibited by escapee (unaffected members of families with HD) or control fibroblasts. The specific activity of glyceraldehyde 3-phosphate dehydrogenase (GAPDH) in normally cultured HD fibroblasts was not different from that in control and escapee fibroblasts. However, in escapee and control fibroblasts subjected to stress by withholding fresh medium, the specific activity of GAPDH in cells harvested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
3
9
1
1
Order By: Relevance
“…However, in [41,42]. Another study reported no changes in enzyme activity during resting conditions in fibroblasts from HD patients, but under energy demanding conditions a lower activation of GAPDH was observed, as compared to that shown by fibroblasts from control individuals [43]. The present study shows no changes in basal GAPDH activity, but IOA treatment induced a larger inhibition of the enzyme in transgenic mice, particularly, in the cerebral cortex and the hippocampus.…”
Section: Discussioncontrasting
confidence: 53%
“…However, in [41,42]. Another study reported no changes in enzyme activity during resting conditions in fibroblasts from HD patients, but under energy demanding conditions a lower activation of GAPDH was observed, as compared to that shown by fibroblasts from control individuals [43]. The present study shows no changes in basal GAPDH activity, but IOA treatment induced a larger inhibition of the enzyme in transgenic mice, particularly, in the cerebral cortex and the hippocampus.…”
Section: Discussioncontrasting
confidence: 53%
“…Specific activity was expressed as milliunit (mU)/mg protein. A milliunit was defined as the amount of enzyme required to catalyse the production of 1 nmol NADH per minute (Cooper et al . 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in HD studies, GAPDH has been reported to bind and form a complex with the huntingtin protein (Burke et al, 1996;Cooper et al, 1998).…”
Section: Glyceraldehyde-3-phosphate Dehydrogenasementioning
confidence: 99%